Stability of mesoporous hybrid organosilica materials incorporating a biphenyl moiety - Magdaluyo, Eduardo R., Jr (2007)
The mesoporous hybrid organosilica materials opened up wider range of applications in the fields of catalysis and sensing, separation, chromatography and microelectronics. The distinguishing characteristic of these new materials is the presence of organic bridging groups incorporated into the channel walls of an ordered mesoporous structure. Their thermal and hydrothermal stability, as well as the resistance when exposed to ultraviolet radiation are important factors to consider for long term practical applications. We have obtained mesoporous hybrid organosillica materials incorporating a biphenyl moiety. The condensation of tetraethoxysilane with 4,4?-bis (triethoxysily) biphenyl precursor and bis (triethoxysilyl) ethane in basic medium was performed via surfactant-templated synthesis. The stability of the obtained organosilica materials was investigated by calcinations process, hydrothermal test and exposure to 254 nm and 590 nm wavelengths. Moreover, the structural and compositional changes of the hybrid materials were studied under varying amounts of bis (triethoxysilane) ethane and aging temperature during polymerization. The hybrid organosilica materials incorporated with biphenyl moiety were thermally stable up to 700 degree celcius which were supported by infrared spectroscopic and thermal gravimetric analyses. The new materials were hydrothermally stable. This could be accounted for by the strong covalent integration of the organic bridging groups in the silica framework and observed channel wall thickness measuring about 50.71 A. Compositional characterization of the hybrid materials, when exposed to 254 nm and 590 nm wavelengths showed no significant change under the various conditions used for stability testing. Calcination led to the formation of enhanced microsphere particles morphology and had no effect even on the unit cell parameter of the two dimensional hexagonal mesostructure. The interplanar spacing was decreased when aging temperature was varied and the integration of biphenyl moiety in the framework was deceased with increasing amount of bis (triethoxysilyl) ethane. This suggests that the structural and textural properties are tunable to the desired application. The thermal and hydrothermal properties as well as the resistance to ultraviolet radiation of the obtained mesoporous hybrid organosilica materials were analyzed to be stable enough under the conditions specified for this study. It can be concluded that this new material is suitable for long term applications in which these properties are critical.